PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) PADA PEMBELAJARAN KONSEP ROUTING DALAM MATA KULIAH TEKNIK JARINGAN - Raulia Putri, Diva; Anugrah, Septriyan; Kurnia, Reni; Masnur, Alkadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by students' difficulties in grasping abstract routing concepts. The learning process, which remains dominated by standard presentation media and constrained by limited instructional time, hinders students' ability to visualize routing processes. This study aimed to develop valid and practical augmented reality learning media for teaching routing concepts. It employed the Research and Development (R&D) method using the 4D model, comprising the Define, Design, Develop, and Disseminate stages. A practicality test was conducted with 23 students from the Educational Technology study program. Data collection instruments included validation sheets for subject matter experts and media experts, as well as a practicality questionnaire. The results indicate that the developed augmented reality learning media achieved a 96% validation score from the subject matter expert (categorized as "highly valid"), while media experts I and II awarded scores of 98% and 96%, respectively (also categorized as "highly valid"). Furthermore, the practicality test yielded a score of 87.5%, placing it in the "highly practical" category. Based on these findings, it is concluded that the augmented reality learning media is both valid and practical for use in the learning process.